Validasi Metode Analisis Senyawa Enhidrin Dalam Ekstrak Daun Yakon Menggunakan Kromatografi Lapis Tipis (KLT) - Densitometri - Nugroho, Ardi; Prasasti, Syita Shevia; Tamhid, Hady Anshory (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Before using medicinal plant products, quality control is required to determine their quality and consistency. Yacon leaves (Smallanthus sonchifolius) in preclinical trials have pharmacological effects to lower postprandial glucose with enhydrin as the marker compound. This study aimed to develop and validate a TLC-Densitometry method for determining enhydrin in Yacon leave extract. The stationary phase was TLC plates of silica gel GF254, while a mobile phase was the mixture of chloroform:hexane in the ratio of 10:1 was selected for the chromatographic system. Then, the TLC separation was followed by densitometric analysis at 210 nm. The method was validated in terms of linearity, accuracy, precision, limit of detection (LOD), and limit of quantitation (LOQ), and found to be linear, with a correlation coefficient (R2) 0.9998. The LOD and LOQ values calculated from the calibration curve were 80.57 and 244.1µg/mL, respectively. The method also exhibited acceptable precision, with relative standard deviation values lower than 3%. The accuracy of the method was evaluated based on the recovery percentages, and found to be within an acceptable range (97–107%).